Analisis Dampak Kompensasi Digital, Jobdesk terhadap Loyalitas Kerja di AK-Tekstil Solo - Adam Munirul Haq; Agus Suyatno; Primadia Putri Harmastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of information technology has driven significant transformations in human resource (HR) management, including in the aspects of compensation and job description adjustments. Digitalization in HR management not only simplifies administrative processes but also has the potential to increase employee satisfaction and loyalty through transparency, speed, and ease of access to information. This study aims to analyze the effect of digital compensation and job description adaptation on employee loyalty at AK-Tekstil Solo, a labor-intensive company in the textile industry. The research method uses a quantitative approach with a survey design. Data were collected through questionnaires distributed to a number of employees as respondents, then analyzed using multiple regression analysis techniques to test the effect of independent variables on the dependent variable. Digital compensation in this study was measured by aspects of transparency, payment speed, and ease of access, while job description adaptation was assessed by role clarity, task flexibility, and communication between management and employees. The results show that digital compensation designed with a transparent, accurate, and easily accessible system contributes positively to job satisfaction, which in turn increases employee loyalty to the company. Similarly, job description adaptation carried out in a structured manner and accompanied by clear communication has been proven to strengthen employee commitment and attachment to the organization. These findings provide strategic implications for company management, particularly in labor-intensive industries, to develop digital-based compensation systems that are not only efficient but also foster trust and fairness. Furthermore, management needs to ensure job descriptions are adaptive to changes in the work environment so that employees continue to feel valued and relevant to the company's goals. Implementing this strategy is expected to create a stable, productive, and sustainable work environment.